Responses to the Global City: The Urban Question in the Twenty-first Century. A Dialogue with Teresa Caldeira - Ignacio Arce Abarca (Íconos)
Responses to the Global City: The Urban Question in the Twenty-first Century. A Dialogue with Teresa Caldeira.